Evaluación de bases orgánicas para la síntesis de ácido cannabidiólico a partir de cannabidiol (2024)
In this research project, the effect of different organic bases and cocatalysts on the synthesis of cannabidiolic acid (CBDA) from cannabidiol (CBD) was evaluated, with the aim of optimizing the reaction yield. The bases used, such as (1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), potassium t-butoxide (t-BuOK), and an inorganic base such as sodium hydride (NaH), along with metals such as magnesium, zinc, and nickel, achieved yields between 7.3% and 2.5%. Although these results did not significantly surpass those reported in previous studies, the need arises to optimize the process.